Haematological reference intervals of wild southern Australian koalas (Phascolarctos cinereus). Issue 5 (9th February 2020) - Fabijan, J; Speight, N; Boardman, WSJ; Hemmatzadeh, F; Trott, DJ; Woolford, L
Abstract : Objective: Current haematology reference intervals (RIs) for koalas were developed in northern Australian koalas, using low numbers and/or individuals of unknown Chlamydia pecorum and koala retrovirus (KoRV) status. This study developed haematological RIs for wild, clinically healthy southern Australian koalas of known C. pecorum and KoRV infection status and investigated the effects of population, age and sex. Methods: Haematological RIs were determined for 138 clinically healthy South Australian koalas (Mount Lofty Ranges [MLR], n = 68; Kangaroo Island, n = 70) examined in April 2016 and February 2017, respectively. C. pecorum and KoRV status were determined by PCR. Results: RIs for southern koala haematological parameters were established for all koalas based on the finding that there were limited differences in haematological values in koalas with subclinical C. pecorum or KoRV infections (P > 0.05), except KoRV‐infected koalas had a lower haematocrit than noninfected koalas. MLR koalas had significantly lower erythrocyte mass and leucocyte counts than Kangaroo Island koalas. Young koalas had significantly lower haemoglobin, haematocrit and higher mean cellular haemoglobin concentration and lymphocyte counts than adult koalas. MLR male koalas had elevated erythrocyte, leucocyte and neutrophil counts compared with MLR females. Conclusion: The haematological RIs developed in this study are based on a large number of clinically healthy koalas, where subclinical C. pecorum and KoRV infections had no effect on haematological values and will be a valuable tool during clinical examination and disease investigation by veterinarians and researchers Australia‐wide.